Assessing anthropometric and laboratory outcomes of a paediatric telehealth weight management program. (June 2023) - Lukenbill, Timothy; San Giovanni, Christine B; Simpson, Annie; Chew, Marshall; Basco, William; Roberts, James
Introduction: Telehealth can expand quality care to patients unable to access specialty health services. The purpose of this study was to compare changes in body mass index (BMI) and laboratory values in patients visiting a weight management clinic for in-person versus telehealth counselling. Methods: A retrospective cohort study of active program participants from two to 22 years old was conducted. Change in BMI, BMI z-score, low-density lipoprotein (LDL), alanine aminotransferase (ALT), and glycated haemoglobin (HbA1c) levels were measured at each patient's initial and final visit for the study period, and the difference was analysed for significance. Change in BMI z-score was analysed for non-inferiority of the telehealth group using a delta of 0.15. Results: We evaluated 1019 of 1126 (90.5%) in-person patients and 58 of 75 (77.3%) of telehealth clinic patients. The mean initial BMI was 32.2 and 32.6 for the in-person and telehealth groups, respectively. There were mean decreases in BMI z-scores of 0.044 and 0.032 in the in-person and telehealth groups, respectively, P < 0.001 with a margin of 0.15. The changes in mean HbA1c ( p = 0.59), mean LDL ( p = 0.93), and a mean ALT ( p = 0.09) were not significant, although only a minority of patients followed-up for lab draws, limiting interpretation of these results. Discussion: Attending a weight management clinic via telehealth was non-inferior to in-person visits for enacting a clinically significant change in BMI z-score, mitigating the effect of sample size on BMI z-score results. These findings give credibility to telehealth as a means of increasing access to paediatric weight management care.